Intergenerational study: mirrors as a tool for self-reflection. Issue 1 (4th March 2014) - Ridley, Susan
Abstract : Purpose: – This qualitative study was an exploration on the process of self-reflection on identity. The purpose of this paper is to see how mirrors could be used as a therapeutic tool and a meta-physical bridge to one's inner consciousness. Design/methodology/approach: – An intergenerational expressive arts group ( n =12) was organized around the question of identity. Following an open-discussion around the topic of identity, participants were asked to decorate a mirror with words, images, and/or symbols while reflecting on the question, "Who am I?" A post-session interview was conducted regarding participant's experiences during the creative process. Findings: – The results indicated that mirrors can be used to connect to one's inner thoughts and feelings on the question of identity. Three core themes in the process of self-reflection on identity were revealed which included introspection and self-concern, connection and attachment to something or someone other than self, and taking action to help others. Research limitations/implications: – This study was limited not only in size, but also in cultural diversity and disparity of age range. Although this study was limited, it provided a useful indicator for identifying core themes in the process of self-reflection on identity. Originality/value: – While there have been no studies on the therapeutic use of mirrors as a tool for self-reflection and limited intergenerational studies with pre-adolescent and adolescent students and older adults, results from this study will add to the body of expressive arts literature by providing a new metaphor for mirrors as a therapeutic tool for self-reflection on identity.